Pengaruh penggunaan superplasticizer admixtures terhadap susut beton usia muda - Mohammad Junaedy Rahman; Ahmad Rifqi Asrib; Irma Aswani Ahmad; Aulia Meylinda Al Farkah (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Early-age concrete shrinkage, caused by the loss of water and the hydration reaction process, can lead to micro-cracks that propagate into sources of weakness, thereby reducing the concrete's serviceability and durability. The long-term effects of this issue can be mitigated through the interlocking effect of aggregate grading and/or the addition of non-shrinkage admixtures. Type F admixtures classified as high-range water reducers (HRWR) or superplasticizers can increase workability, reduce volumetric deformation without compromising the concrete's mechanical properties. This study specifically aims to determine the influence of superplasticizer on reducing shrinkage and enhancing the compressive strength performance of concrete. The early-age shrinkage study was conducted by measuring vertical strain changes in fresh concrete cylinder specimens cast in molds with leveled surfaces containing both fine and coarse aggregates, a composition that yields different shrinkage behavior compared to tests typically performed on mortar. Simulations involving the addition of superplasticizers at dosages of 0.35%, 0.55%, and 0.75% by weight of cement showed positive effects on slump and density; furthermore, these dosages resulted in progressively lower shrinkage values ??by the end of the 330-minute measurement period. A comparison of concrete shrinkage measurements on test specimens without superplasticizer admixtures revealed shrinkage values ??of 58.16%, 71.11%, and 85.37% for the respective dosage categories of 0.75%, 0.55%, and 0.35%. These results demonstrate that early-age concrete shrinkage can be significantly reduced through the addition of superplasticizers. Additionally, the use of these superplasticizer dosages indicated an increase in compressive strength beyond the design grade at 28 days. Regression analysis using a power-law equation yielded a coefficient of determination (R²) of 99.79%, strongly indicating that early-age shrinkage influences the concrete's compressive strength.